PROSES KERJA SAMA MEDIA PARTNER PADA ACI – FMA (ASSOCIATION COMBISTE INTERNATIONALE – FINANCIAL MARKET ASSOCIATION) WORLD CONGRESS - rizkiningdita, Nisya maulida; Pranita, Diaz (UI Scholars Hub, 2018)
The focus of this study is to discuss the process of approaching media partner in ACI world Congress 2016 event that is organized by PT. Fasen Creative Quality. This research is qualitative descriptive interpretive. The research uses Observation, interview, and Study of Literature as the writing method. Researchers found that ACI World Congress 2016 has many media partners both national and international media which join to publish the event. The results also revealed that there are five process in approaching mesdia partner used are data validation, offering letter, letter of agreement, publishing, and report of advertising.